Arduino solar tracker with blynk / Muhammad Azim Hafizi Azlan - Azlan, Muhammad Azim Hafizi (2024)
This extensive abstract describes an innovative Internet of Things (IoT)-enabled Arduino solar tracking system that aims to maximize solar panel performance by dynamically altering the panels' position throughout the day. Using IoT connectivity for remote accessibility and Arduino microcontrollers for accuracy and versatility, this modern invention marks a substantial advancement in solar technology. The system maximizes solar energy capture by ensuring correct panel alignment in real-time through the use of servo motors, light sensors, and an intelligent algorithm. The Arduino board serves as the main control unit, coordinating panel movements and allowing online or mobile application-based remote monitoring and control. By increasing solar panel efficiency, this connectivity not only improves the system's technical capabilities but also advances sustainable energy options. Beyond technological developments, this project represents an important step toward the general acceptance of renewable energy practices. It provides a clever, flexible, and effective solution that has the potential to change how solar energy is used in the future in order to create a more sustainable environment. In order to ensure both functionality and efficiency, the process went further by designing and integrating the Arduino board, light sensors, and servo motors as part of the solar tracking system. These steps were followed by careful testing. The results show major improvements in capturing electricity efficiency, confirming that the sun tracking system is a useful tool for optimizing solar panel performance. In summary, the project presents an effective use of Internet of Things-enabled solar tracking technology and presents an achievable method to improve renewable energy practices and make a positive impact on a more sustainable future.